Literature Review : "Transforming Conflict Into Harmony: A Philosophical Approach In Organizational Management" - Rr Suci Palasari; Asep Dana Saputra; Heri Pratikto; Agung Winarno (International Journal of Economics, Business and Innovation Research, 2024)
Conflict is a fundamental aspect of human interaction, spanning individual, group, and organizational levels. Traditionally viewed as a barrier, modern perspectives recognize conflict as a catalyst for innovation and system improvement when managed effectively. Philosophical approaches to conflict management emphasize the importance of understanding its roots and leveraging differences constructively, integrating principles of justice, ethics, and communication. This shift in approach-from avoidance to one of strategic engagement-positions conflict as an opportunity for growth and harmony within organizational contexts. The paper examines conflict dynamics through its types, causes, and impact, therefore showing its dual nature to either disrupt or improve organizational process. Conflicts arise out of various reasons relating to resource limitation, cultural differences, and breakdowns in communication, which, when responded to with philosophical insights, can result in creative problem solving and increased productivity. This research by the authors emphasizes a structured approach-from identifying conflict and analyzing its causes to implementing the solution and evaluating it-as the only way to convert challenges into opportunities.A holistic approach will enable the organization to redefine conflict as part of harmony. The various approaches to conflict management at a philosophical level will encourage collaboration, creativity, and synergy in promoting organizational elasticity in a turbulent environment. These results plead for ethical, inclusive strategic conflict resolution that will help to attain continuous development with cohesive interpersonal or intergroup relationships.